KEPATUHAN PEMASANGAN RUMPON TERHADAP PERATURAN KEMENTERIAN KELAUTAN DAN PERIKANAN DI PELABUHANRATU - Ricky Dameanus Sembiring Depari; Darmawan Darmawan; Thomas Nugroho (Fakultas Perikanan dan Ilmu Kelautan, 2022)
The use of FADs can help fishermen reduce fuel consumption, speed up fishing location, shorten days of operation, and reduce operating costs. However, negative impacts also arise such as conflicts with other fishermen and the potential for overfishing. The Ministry of Maritime Affairs and Fisheries has issued regulations regarding the use of FADs to prevent those negative impacts. The regulation will be successful if it is implemented and obeyed by the fishermen who are the purpose of the regulation. However, it is currently unknown whether the fishermen in Pelabuhanratu know, understand and comply with these regulations. Therefore, this study aims to find out the level of compliance of Pelabuhanratu fishermen with formal rules from the government and informal rules among themselves. The research was conducted through interviews with capital owners, captains, and crew members. It was conducted from August to October 2017. Analysis of the results of the interviews was carried out descriptively and equipped with Likert analysis. The results show that the capital owners know and understand the existing regulations but do not comply with them. The captain and crew carry out their own social ethics among themselves to respect each other's FADs, sanctions for transgression/theft and responsibilities towards their FADs, but do not pay attention to any formal regulations from the government.